Personality and Chinese adolescents' career exploration: The mediation effects of self-efficacy and perceived parental support. (2019) - Wang, Jiaying; Fan, Weiqiao; Cheung, Fanny M.; Wang, Qian; Li, Mengting
The study compared the contributions of self- and social-oriented personality factors to Chinese adolescents' career exploration with a longitudinal perspective. The mediation effects of career decision self-efficacy and perceived parental support were also investigated. A total of 488 high school students in Hong Kong took three waves of a questionnaire survey at Grade 10, Grade 11 and Grade 12 respectively. The results indicated that adolescents' career exploration at Grade 12 could be predicted by both self- and social-oriented personalities at Grade 10. Specifically, both self- and social-oriented personality factors could contribute to adolescents' environmental exploration, and the effect was mediated by perceived parental support at Grade 11, after controlling for the effect of career exploration at Grade 11; whereas self-oriented personality factor could contribute to self-exploration, and the effect was mediated by career self-efficacy at Grade 11. The implications for career counseling and education for Chinese adolescents are discussed.